The Impact of Single Agents on Gender Equityin Organizations – The Case of Austrian Equal Opportunity Active Works Councillors; Der Einfluss von einzelnen Akteur/innen auf betriebliche Gleichstellungspolitik – am Beispiel von gleichstellungsaktiven Betriebsrät/innen in Österreich - Manfred Auer; Heike Welte (Industrielle Beziehungen, 2013)
The aim of this article is to explore the influence of single agents on gender equity in organizations. In our qualitative study, we focus on works councillors as equal opportunity agents in large profit organizations in Austria, because of their unique institutional position regarding organizational change in the direction of gender equity. This study is based on the concept of social positioning within the theory of structuration (Giddens 1992). We organize our empirical material along Stones' (2005) conception of the `quadripartite nature of structuration', including external and internal structures, activities and outcomes. In the discussion of reasons for the rather limited impact equal opportunity active works councillors have on gender equity, we emphasize the constitutive approach of co-determination and a liberal concept of equal opportunity policies. Accordingly, works councillors broadly accept gendered structures in organizations and mainly deal with obvious, unfair (formal) procedures or individual cases of discrimination as the outcomes of these structures. – – Zielsetzung dieses Artikels ist es, den Einfluss von Gleichstellungsakteur/innen auf Chancengleichheit der Geschlechter in Organisationen zu untersuchen. Grundlage dafür bilden qualitative Interviews mit gleichstellungsaktiven Betriebsrät/innen in großen privatwirtschaftlichen Unternehmen in Österreich. Wir konzentrieren uns auf Betriebsrät/innen, da diese Akteur/innen institutionalisierte Möglichkeiten der Förderung, Kontrolle und Initiierung von Gleichstellungsmaßnahmen in Organisationen haben. Den theoretischen Rahmen bildet das Konzept der sozialen Positionierung als Teil der Strukturationstheorie von Giddens (1992). Die Daten werden anhand der vier Dimensionen der `quadripartite nature of structuration' (Stones 2005) organisiert: externe Strukturen, interne Strukturen, Aktivitäten und Ergebnisse. Die Gründe für den von uns konstatierten geringen Einfluss gleichstellungsaktiver Betriebsrät/innen auf betriebliche Chancengleichheit der Geschlechter liegen vor allem in den institutionellen Rahmenbedingungen betrieblicher Mitbestimmung sowie eines liberalen Konzepts von Gleichstellungspolitik. Betriebsrät/innen akzeptieren weitgehend vorhandene geschlechtsspezifische Strukturen in Organisationen und agieren in erster Linie bei offensichtlich diskriminierenden Verfahren oder in einzelnen Fällen von Diskriminierungen.
Keywords: J00; J59; J70; J83; 330; gender equity; works councillors; social positioning; structuration theory; Austria